IMPELEMENTASI PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PEDESAAN (PUAP) DI KECAMATAN MUARA SABAK TIMUR KABUPATEN TANJUNG JABUNG TIMUR - Ningsih Sutrisno, Trias; Alamsyah, Zulkifli; Lubis, Arsyad (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2018)
This study aims to: (1) Study PUAP program implementation by farmers in the Eastern District of Muara Sabak and (2) Analyzing socio-economic factors that influence the success of the PUAP program in East Muara Sabak. The data used are primary data obtained through interviews directly to related parties as well as questionnaires. PUAP Program implementation is presented descriptively quantitatively using statistical analysis techniques paired samples t test (paired sample t-test). Meanwhile, to analyze the socio-economic factors that influence the success of PUAP used multiple linear regression models. The results showed as much as 97.18% of farmers use PUAP funds for the purchase of fertilizers and pesticides in production activities. The remaining 2.8% of the funds used by farmers for consumption activities. Testing changes in farm incomes before and after the show PUAP t value of 8,574 with a significant level of 0.000. This shows there is a real and significant differences in farm income before and after the PUAP. While the test results PUAP factors that influence the success shows that a variable number of dependents, land and farming experience positive and significant impact on the success of PUAP. While the variables of age and education did not significantly influence the success of PUAP.